Experience report: environmental education on the trails of CECT Brasital - Silva, Rogério de Souza; Martins, Wagner Lelis Coelho (Revista Hipótese, 2019)
This article is an account of the extension project called "Ecotourism in Brasital: an experience of historical, cultural and environmental tourism in São Roque", which occurred in the years 2015 to 2017. Project developed in the municipal historical-cultural heritage Educational Center, Cultural and Tourism (CECT) Brasital, a town that has a large forest area known as "Waterways", carried out, in the first year, a survey of the fauna and mapping of its ecological trails. In the following two years he focused on environmental monitoring for tourists and visitors to CECT Brasital. From these initial actions, it is inferred that the practice of ecotourism can contribute, in a decisive way, in the cultural and environmental preservation of historical heritage.